Are we Practicing Evidenced Based Medicine for Common Paediatric Problems? - Sharma, Pushpa Raj (Journal of Nepal Paediatric Society, 2009)
doi: 10.3126/jnps.v29i2.2039 J. Nepal Paediatr. Soc. Vol 29, No. 2, pp.57-58